New species and subspecies of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from Taiwan - Shavrin, Alexey V. (Zootaxa, 2015)
Two new taxa of the genus Lesteva Latreille, 1797 from Taiwan (Hualien County) are described and illustrated: L. smetanai sp. n. and L. rufopunctata taiwanica subsp. n. A key to species known from Taiwan is provided.